2020
DOI: 10.3389/fpls.2020.00550
|View full text |Cite
|
Sign up to set email alerts
|

Spring Leafing Phenology Favors Younger Culms of Moso Bamboo: Aspects From Water Use Relations

Abstract: As the most widely distributed giant running bamboo species in China, Moso bamboo (Phyllostachys edulis) can accomplish both development of newly sprouted culms and leaf renewal of odd-year-old culms within a few months in spring. The two phenological events in spring may together change water distribution among culms in different age categories within a stand, which may differ from our conventional understanding of the negative age effect on bamboo water use. Therefore, to explore the effect of spring shootin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The influence of ramet age, phenology, and drought on the transpiration of moso bamboo was studied in Guilin Botanical Garden in Southern China, which has a subtropical monsoon climate [34]. The mean annual air temperature of the site was 19.3 • C. The study showed that the daily maximum sap flux density was higher, which lead to an increasing transpiration rate in less than >3-year-old ramets, results which are similar to those reported by [32]. The above results showed that the transpiration of moso bamboo was influenced by culm age, phenological stages, and soil moisture content.…”
Section: Factors Affecting Bamboo Phenologysupporting
confidence: 74%
See 1 more Smart Citation
“…The influence of ramet age, phenology, and drought on the transpiration of moso bamboo was studied in Guilin Botanical Garden in Southern China, which has a subtropical monsoon climate [34]. The mean annual air temperature of the site was 19.3 • C. The study showed that the daily maximum sap flux density was higher, which lead to an increasing transpiration rate in less than >3-year-old ramets, results which are similar to those reported by [32]. The above results showed that the transpiration of moso bamboo was influenced by culm age, phenological stages, and soil moisture content.…”
Section: Factors Affecting Bamboo Phenologysupporting
confidence: 74%
“…It can be summarized that the leaf phenology can be altered to grow according to the environmental conditions under which they will survive. With regards to physiological processes related to bamboo phenology, water use in moso bamboo (P. edulis) was examined [32] according to spring leafing phenology with four different culm ages, which were newly sprouted, at 1, 2, and 3 years old, at Zhejiang A&F University, Hangzhou, China. The mean annual temperature of the study site from 2008 to 2017 was 17.6 ± 0.4 • C. The tested 3-year-old culms were found to have the least water utilization compared to other age culms during the experimental period from March to June 2018.…”
Section: Factors Affecting Bamboo Phenologymentioning
confidence: 99%
“…This study included three age categories of culms: newly sprouted culms less than 1-year-old (the leaf formation was completed in June 2021), 2 or 4 years old (the leaf formation was completed in June 2020), and 6 or 8 years old (the leaf formation was completed in June 2020), referred to as young, mature, and old, respectively. The age of the selected culms was determined according to Mei et al (2020). The crowns of the selected bamboo culms were intact, unbroken, and unaffected by visible diseases or pests.…”
Section: Site Description and Bamboo Stand Selectionmentioning
confidence: 99%
“…The study site locates in the Pingshan experimental base of the Zhejiang A&F University, Lin an, Zhejiang Province of China. Zhejiang Province is located in southeast China and belongs to a typical subtropical monsoon climate zone with an average temperature of 17.6 ± 0.4 • C and an average annual rainfall of 1,579.7 ± 263.5 mm from 2008 to 2017 (data obtained from the National Meteorological Information Center; http:// data.cma.cn/site/index.html) (Mei et al, 2020;Tong et al, 2021).…”
Section: Study Site and Treatment On Experimental Sample Culmsmentioning
confidence: 99%